Linear Sclerodermoid Lupus Erythematosus Profundus in a Child. (December 2016) - Elbendary, Amira; Griffin, John; Li, Suzanne; Tlougan, Brook; Junkins-Hopkins, Jacqueline M.
Abstract : Abstract: Lupus erythematosus panniculitis, also known as lupus profundus, is a variant in the clinicopathological spectrum of lupus erythematosus (LE) affecting about 2%–3% of LE patients. A linear configuration of LE panniculitis has been reported rarely with rare reports describing the coexistence of different forms of cutaneous LE and localized morphea. In this study, the authors present a 9-year-old girl with linear arrangement of subcutaneous nodules on her left forearm. Microscopic findings from 2 biopsies included lymphocytes at the dermoepidermal junction with mild interface dermatitis, a dense lymphocytic infiltrate that was concentrated around adnexae and subcutaneous fat in concert with thickened collagen bundles and mild widening of fibrous septae surrounding fat lobules. Although the clinical differential diagnosis included panniculitis or a sporotrichoid infection, 1 biopsy showed a dense lymphocytic infiltrate histologically bordered on that of cutaneous lymphoid hyperplasia or a late stage of Lyme disease, and a second also demonstrated more prominent sclerodermoid collagen bundles rendering the diagnosis of linear sclerodermoid LE profundus.